Optimum design of acoustic stealth shape of underwater vehicle model with conning tower - Tang, Yuhang; Wang, Xueren; Miao, Xuhong; Gao, Shengyao; Li, Bing; Peng, Zilong (Frontiers in Physics, 2023)
The development of underwater acoustic countermeasure technology has increased research interest in the design of acoustic stealth shapes for underwater vehicles. In this research, the component superposition method based on phase interference was adopted to simplify and decompose a non-axisymmetric complex underwater vehicle model into two main parts: the hull and the conning tower. By using the COMSOL-MATLAB integrated software as the platform, the optimization algorithm, mathematical description of the shape of underwater vehicle hull, and planar element method (PEM) were combined to develop a set of optimization methods for underwater vehicle acoustic stealth in the free field. This method can be utilized to realize the automatic optimization design of acoustic stealth shapes for underwater vehicle model in a given frequency band and acoustic incident angle range. The optimized underwater vehicle design has a smooth appearance and low target strength (TS) and angle detection rate for most detection angles and frequency bands. The optimization design method may provide guidance for the lower TS shape design of the underwater vehicle.